MgtE from Rhizobium leguminosarum is a Mg2+ channel essential for growth at low pH and N2-fixation on specific plants - Hood, G; Karunakaran, R; Downie, A; Poole, P (American Phytopathological Society, 2015)
MgtE is predicted to be a Rhizobium leguminosarum channel that is essential for growth when both Mg2+ is limiting and the pH is low. N2 was only fixed at 8% of the rate of wild type when the crop legume Pisum sativum was inoculated with an mgtE mutant of R. leguminosarum and although bacteroids were present, they were few in number and not fully developed. R. leguminosarum MgtE was also essential for N2-fixation on the native legume Vicia hirsuta but not when in symbiosis with Vicia faba. The importance of MgtE and the relevance of the contrasting phenotypes is discussed.